2014
DOI: 10.1242/dev.099002
|View full text |Cite
|
Sign up to set email alerts
|

Msx1 and Msx2 act as essential activators of Atoh1 expression in the murine spinal cord

Abstract: Dorsal spinal neurogenesis is orchestrated by the combined action of signals secreted from the roof plate organizer and a downstream transcriptional cascade. Within this cascade, Msx1 and Msx2, two homeodomain transcription factors (TFs), are induced earlier than bHLH neuralizing TFs. Whereas bHLH TFs have been shown to specify neuronal cell fate, the function of Msx genes remains poorly defined. We describe dramatic alterations of neuronal patterning in Msx1/Msx2 double-mutant mouse embryos. The most dorsal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…Nevertheless, Pax3/7/pax-3 and Msx/ vab-15 still express in the lateral border of the CNS neuroectoderm in worm (15,33), consistent with the conserved expression patterns of these two lateral genes in arthropods, annelids, and chordates (8). Our genetic analysis shows that both Msx/vab-15 and Pax3/7/pax-3 specify P neuroblasts, which are worm CNS progenitors, similar to their roles in the lateral CNS progenitors in fly and vertebrates (11,16,(34)(35)(36). Combining our data with the existing evidence of the common origin of trunk CNS from fly to vertebrates (8,27), it is more likely that nematodes inherited the Msx/vab-15 specification of P neuroblasts from Urbilateria than the nematode branch lost the conserved lateral domain after diverging from fly and then regenerated it independently.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, Pax3/7/pax-3 and Msx/ vab-15 still express in the lateral border of the CNS neuroectoderm in worm (15,33), consistent with the conserved expression patterns of these two lateral genes in arthropods, annelids, and chordates (8). Our genetic analysis shows that both Msx/vab-15 and Pax3/7/pax-3 specify P neuroblasts, which are worm CNS progenitors, similar to their roles in the lateral CNS progenitors in fly and vertebrates (11,16,(34)(35)(36). Combining our data with the existing evidence of the common origin of trunk CNS from fly to vertebrates (8,27), it is more likely that nematodes inherited the Msx/vab-15 specification of P neuroblasts from Urbilateria than the nematode branch lost the conserved lateral domain after diverging from fly and then regenerated it independently.…”
Section: Discussionsupporting
confidence: 75%
“…Previous in vivo studies have shown that Lmx1a is sufficient for roof plate induction and several components of roof plate signaling, including BMP4, GDF7 and Wnt1 (Chizhikov and Millen, 2004a). These signals are all essential for dorsal spinal cord patterning, but their roles depend on the factors and their downstream targets, such as MSX1-3 (Duval et al, 2014; Chizhikov and Millen, 2005; Liu et al, 2004). A future investigation of hPSC-derived spinal cord induction should focus on the mechanistic analysis, especially with regards to the factors that determine the self-organization of patterned spinal cord neuroepithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study shows that Msx1 and Msx2 , two homeodomain transcription factors that are induced earlier than bHLH transcription factors, likely play a role as transcriptional activators of Math1 / Atoh1 in spinal cord development (Duval et al, 2014). The dI1A (also known as dI1 comm ) neurons express the Lim-HD transcription factors Lhx2 high and Lhx9 low , while dI1B (also known as dI1 ipsi ) express the Lim-HD TF Lhx9 (Helms and Johnson, 1998; Lee et al, 1998; Bermingham et al, 2001; Gowan et al, 2001; Wilson et al, 2008; Avraham et al, 2009).…”
Section: Dorsal Interneuron Progenitorsmentioning
confidence: 99%